Analisis Faktor-Faktor yang Mempengaruhi Produksi Usaha Tani Jagung: Kasus Kecamatan Geyer Kabupaten Grobogan Jawa Tengah - Tiurlina Ade Novelin Br Purba; Purbayu Budi Santosa (Diponegoro Journal of Economics, 2023)
This study aims to analyze the factors of production that affect the amount of corn farming production in Geyer District, Grobogan Regency. This study uses primary data with a questionnaire technique. The number of samples in this study was obtained from 100 farmer respondents. Completion of the number of samples to be taken is determined by the Slovin formula. This study uses the Cobb-Douglas production function to determine the coefficients of the regression of production factors consisting of seeds, large land area, labor, fertilizers, and pesticides on corn production. The results showed that the production factors that significantly influence corn production are seeds and land area. While the other 3 variables, namely labor, fertilizer, and tickets, have no significant effect. The corn production function in Geyer District, Grobogan Regency is in a Return to Scale condition of 1.05467, which indicates increasing returns because the Return to Scale coefficient is above 1, this is because the production factors used can still be increased.